Anatomical Left Superior Vena Cava Correction: An Option for Left Ventricular Recruitment? - Bieling, Frederike; Cesnjevar, Robert A.; Cuomo, Michela; Weigelt, Annika; Dittrich, Sven; Purbojo, Ariawan (The Thoracic and Cardiovascular Surgeon, 2025)
Left superior vena cava (LSVC)-related obstruction of mitral inflow is a rare condition in patients with complex cardiac anomalies like hypoplastic left heart complex. We report on the impact of establishing LSVC to right superior vena cava (RSVC) continuity on the growth of borderline hypoplastic left ventricular structures as an addendum to our previously published work.Twenty-two patients underwent LSVC to RSVC anastomosis, whereas six had LSVC ligation (n = 4) or clip closure (n = 2), all alongside congenital heart defect correction. The indication was LSVC-related obstruction of left ventricular inflow due to a dilated coronary sinus. Clinical data were systematically reviewed, with regular follow-up. Left ventricular end diastolic diameters (LVEDD), aortic valve diameters, and left ventricular outflow tract (LVOT) diameters were recorded using echocardiography.Follow-up showed 90% survival at 3.3 ± 0.4 years. Mean LVEDD Z-scores improved from −2.19 ± 0.35 to −1.24 ± 0.26 after repair (p < 0.01) and to −1.33 ± 0.56 at 6-month follow-up. In patients without mitral repair, LVEDD Z-scores improved from −2.11 ± 0.62 preoperatively to −1.85 ± 0.88 postoperatively (p < 0.05). LVOT Z-scores increased from −2.49 ± 0.48 to −0.87 ± 0.75 (p < 0.05) and aortic valve Z-scores improved from −1.08 ± 0.57 to 0.5 ± 0.39 over 24 months (p < 0.05).Anatomical LSVC correction may improve left ventricular filling and growth of the left ventricle, aortic valve, and LVOT in patients with borderline left ventricles and could be considered without as a potential recruitment strategy.
Keywords: aortic valve and root; cardiac anatomy/pathological anatomy; congenital heart disease; echocardiography (all modalities, applications); anatomy; aorta/aortic